Creating Competitive Advantage for MSMES through the Use of Information Technology Functions and Absorptive Capacity in MSMES Priangan Timur - West Java - D Munandar,; J Sarwono,; A Nisa, (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to find out how to create competitive advantage through the use of information technology and the ability to absorb knowledge in MSMEs in the East Priangan area, West Java. In this research, the researcher uses a sequential mixed method where qualitative research is carried out first and then followed by quantitative research. A total of 120 MSME entrepreneurs were selected as respondents purposively and 3 people were used as resource persons (expert judgment method). Linear regression was used to analyze quantitative data. The results of the research show that qualitatively information technology plays a very important role for the sustainability of the business of MSME entrepreneurs in East Priangan, West Java. The ability to absorb knowledge (absorptive capacity) of MSME entrepreneurs has been sufficient. The competitive advantage of the East Priangan MSME managers is sufficient. The results of quantitative research show that the competitive advantage function of MSMEs in East Priangan can be improved through information technology and Absorption Capability, both simultaneously and partially